Patient preferences regarding treatment options for Waldenström's macroglobulinemia: A discrete choice experiment. (26th July 2022) - Amaador, Karima; Nieuwkerk, Pythia T.; Minnema, Monique C.; Kersten, Marie José; Vos, Josephine M. I.
Abstract: Introduction: Treatment options for Waldenström's Macroglobulinemia (WM) have expanded rapidly in the last decades. However, there is no consensus on a preferred treatment. Therefore, patient preferences become increasingly important in making individualized treatment plans. Still, WM patients' priorities and perspectives regarding their treatment options are unknown. We evaluated treatment preferences of WM patients using a discrete choice experiment (DCE). Methods: A mixed‐method approach was utilized for identification and selection of attributes/levels. The DCE questionnaire included five attributes: type of agent (targeted versus chemotherapy); frequency and route of administration; 5‐year progression‐free survival (PFS); adverse events; and risk of secondary malignancies. An orthogonal design and a mixed logit panel data model were used to construct choice tasks and assess patient preferences, respectively. Results: Three hundred thirty WM patients participated in the project. In total, 214 (65%) complete questionnaires were included for data analysis. The 5‐year PFS, followed by risk of secondary malignancies were the most important attributes for making treatment choices. Regarding side effects, patients chose to avoid neuropathy the most compared to nausea/vomiting and extreme fatigue. Patients preferred a fixed‐duration treatment with IV/SC administration at the hospital over a continuous daily oral regimen at home. Conclusion: These are the first systematic data obtained on WM patient preferences for treatment. The results may help discussions with individual patients about their treatment choices. Also, these data can help design clinical trials in WM and inform health‐care decision‐making regarding outcomes that are most relevant to patients. Abstract : When asked about treatment preferences, WM patients prioritize avoiding the risk of secondary malignancies, avoiding peripheral neuropathy as a side effect, prefer targeted therapy over chemotherapy, but prefer fixed‐duration iv/sc over long‐term oral treatment. A treatment regimen that matches all these priorities is currently not available for WM.